A New RF Satellite Link Analyzing and Antenna Effect on Satellite Communication br - Calisir, Bircan; Akbal, Ayhan (Univ North, 2022)
Satellite communications (SatComs) recently, have admitted as a new technological advances that attractedand raised special investment and ventures. Space communication technology has found many application areas from costly, one-of-a-sort structures, to utilize again of technology on sequential tasks, to the progress of canonical protocols accepted by space agencies of lots of countries. Satellite communication has accepted as one of the important technologies for 5G backhauling, particularly on bandwidth request increased in 5G mobile broad band (eMBB) applications. This paper presents the efficiency of the satellite communication system using 16 QAM digital modulation technique for the X band. This digital modulation method presents high data rate in transmission without raising the bandwidth compared with other digital modulation methods. Applications are realized in Matlab environment and obtained conclusions are discussed such as power spectrum diagrams, constellation schemas and BER ratio for several bands such as 4, 8, 12, 16 GHz
Keywords: antenna arrays; satellite communications; 5G